The evolution of Greek fauna since classical times - Sidiropoulos, Konstantinos; Polymeni, Rosa-Maria; Legakis, Anastasios (The Historical Review/La Revue Historique, 2017)
This article concerns the Greek fauna of classical and late antiquity and changes up to the present day. The main sources for the fauna of antiquity are historical, geographical and zoological texts, as well as descriptions from travellers who visited Greece. The study of the texts of classical and late antiquity was based on the following classical authors: Xenophon, Aristotle, Aristophanes Byzantios, Pliny, Dio Chrysostom, Plutarch, Pausanias and Aelian. Some species that were present in the Greek fauna of classical and late antiquity, such as the lion and the leopard, are today extinct in Greece, whereas some other species that are now common, such as the cat, the chicken and the peacock, were introduced about that time or a little earlier from other regions. Some other species that are also common today, such as the wild rabbit and the pheasant, were unknown at that time, as they appeared later in Greece from other areas.